2019
DOI: 10.5334/dsj-2019-048
|View full text |Cite
|
Sign up to set email alerts
|

Data Sharing at Scale: A Heuristic for Affirming Data Cultures

Abstract: Addressing the most pressing contemporary social, environmental, and technological challenges will require integrating insights and sharing data across disciplines, geographies, and cultures. Strengthening international data sharing networks will not only demand advancing technical, legal, and logistical infrastructure for publishing data in open, accessible formats; it will also require recognizing, respecting, and learning to work across diverse data cultures. This essay introduces a heuristic for pursuing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…To arrive at the selection of component topics, an analysis of the initial scoping literature review (Oliver et al, 2023) was considered through a heuristic developed by Poirier and Costelloe‐Kuehn (2019, pp. 4–5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To arrive at the selection of component topics, an analysis of the initial scoping literature review (Oliver et al, 2023) was considered through a heuristic developed by Poirier and Costelloe‐Kuehn (2019, pp. 4–5).…”
Section: Methodsmentioning
confidence: 99%
“…The range of disciplines concerned with data culture/s encompassed the humanities, arts, and social sciences, as well as science, technology, engineering, and mathematics (STEM), but with surprisingly little representation from information studies researchers. We reviewed the full text of each paper to identify how this diverse cohort of researchers understood and portrayed the concept of data culture/s, and we also applied a heuristic developed with the Research Data Alliance (Poirier & Costelloe‐Kuehn, 2019) as an analytical tool to identify the level at which research was focused. We found that there was no unified understanding of what the construct data culture or data cultures represented, and that most publications focused on organizational settings.…”
Section: Preliminary Reviewmentioning
confidence: 99%
“…The selection of participants for this study followed a purposive sampling strategy [45], aimed at eliciting first-order perspectives from researchers who self-reported that they had previously engaged in data reuse as well as second-order perspectives from intermediaries who, in various capacities, had worked to facilitate data reuse by researchers and so could describe their perceptions (veridical or otherwise) of the factors influencing researcher data reuse. In contrast to studies of data reuse that emphasize attunement to particular "data cultures" [46], we aimed to maximize variation with respect to attributes like research field so as to be able to advance a more general set of claims. At the time the study was conducted, our institutions did not require approval for this type of study by an institutional review board or ethics committee.…”
Section: Methodsmentioning
confidence: 99%
“…Adopting persistent identifiers in different research fields will be challenging, as each discipline has its own data culture and jargon that complicates the use of shared schemas, registries, controlled vocabularies and ontologies (Poirier and Costelloe-Kuehn, 2019). There will be no common standard that is meaningful for the variety of experimental techniques used across different subdisciplines (Stocker et al, 2020).…”
Section: Interoperable: Envisioned Challengesmentioning
confidence: 99%